2013
DOI: 10.1007/s10585-013-9569-6
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of miR-126 correlates with metastatic recurrence of hepatocellular carcinoma

Abstract: The liver transplant (LT) situation represents an attractive model for studying hepatocellular carcinoma (HCC) metastasis. Based on microarray data, we previously found that miR-126 expression was lower in tumor tissues of patients with post-LT HCC recurrence compared with non-recurrence. In this study, we examined the expression of miR-126 in HCC samples from 68 patients who had undergone LT using quantitative real-time PCR and analyzed its correlation with clinicopathological features and prognosis of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…Sun, et al showed that miR-126, through targeting EGFL7, may suppress A549 cell proliferation in vitro , and inhibit tumor growth in vivo [9]. Chen et al revealed that decreased expression of miR-126 is associated with metastatic recurrence of HCC [19]. Consistent with previous studies, our results indicated that down-regulation of miR-126 was detected in the HCC tissues and associated with tumor size and liver cirrhosis.…”
Section: Discussionsupporting
confidence: 89%
“…Sun, et al showed that miR-126, through targeting EGFL7, may suppress A549 cell proliferation in vitro , and inhibit tumor growth in vivo [9]. Chen et al revealed that decreased expression of miR-126 is associated with metastatic recurrence of HCC [19]. Consistent with previous studies, our results indicated that down-regulation of miR-126 was detected in the HCC tissues and associated with tumor size and liver cirrhosis.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, low expression of miR-194 in the preexisting advanced adenoma could be a predictor for adenoma recurrence. This hypothesis was supported by a clinical study performed by Chen and colleagues, in which the low expression of miR-126 in liver tissues was significantly associated with tumor recurrence in patients with HCC who underwent liver transplantation (27). Certainly, we also should investigate whether the expression of miR-194 is downregulated in the normal colon mucosa and recurrent adenoma of the patients.…”
Section: Discussionmentioning
confidence: 72%
“…For example, decreased expression of miR-126 in HCC has been correlated with HCC recurrence and poor survival after liver transplantation [30]. In another study, a predictive score combining the expression levels of miR-214, miR-3187 and the Milan criteria was proposed to stratify patients according to their risk for recurrence of HCC and death after liver transplantation [31].…”
Section: Discussionmentioning
confidence: 99%